Upaya Guru Dalam Menangani Kesulitan Belajar Membaca Siswa Kelas 2 SDN 45 Mataram - Berliani, Dwi Sinta; Witono, A. Hari (Primera Educatia Mandalika: Elementary Education Journal, 2024)
This research is motivated by the existence of students who have not been able to read correctly and have difficulty in understanding the meaning of each word or sentence read. Based on this background, the purpose of this study is to describe the teacher's efforts in overcoming reading learning difficulties of grade 2 students at SDN 45 Mataram. This research uses qualitative research with a descriptive approach. The subject of this research is the grade 2 teacher, while the object of this research is grade 2 students at SDN 45 Mataram. The methods used in data collection are observation, interview, and documentation methods. Data analysis techniques are carried out with stages of analysis, namely data collection, data reduction, data presentation, and conclusion drawing. The results of this study show learning problems of students who have difficulty reading and social problems of students who have difficulty reading in class.